Acceptability and Analysis of The Proximate of Instant Porridge Breast Milk Complementary Food (MP-ASI) with Toman Fishmeal Substitution (Channa micropellets) for Infants Aged 6-9 Months Based on Local Food - Ambriani Lestari; Martinus Ginting; Nopriantini Nopriantini (Universitas Negeri Semarang, 2024)
Background: Complementary foods for breast milk (MP-ASI) are foods or drinks that contain nutrients to meet the nutritional content of infants or toddlers as a substitute for breast milk in infants over 6 months of age. Instant porridge is a porridge that is served practically. Toman fish is a local food that can be used to develop MP-ASI. The benefits of Toman fish are helping the growth and development of children's bones, improving brain performance, preventing heart disease, containing proteins that help replace damaged cells, and supporting wound healing. Objective: To determine the acceptability and analysis of nutrient content of instant porridge breast milk supplement (mp-asi) with toman fish meal substitution (Channa micropeltes) for infants aged 6-11 months based on local food from the North Kayong region. Method: This study used an experimental method consisting of 3 treatments of toman fishmeal formulation: F1 (15 grams), F2 (20 grams), and F3 (25 grams). The test is carried out through 2 stages, namely, the organoleptic test and the proximate test. Results: The results showed the best value of F2 nutritional analysis of instant porridge flour with tomato meal substitution showed that the concentration of tomato fish meal in the selected treatment was F2 (20 grams) with the content of fat 26.02 grams, protein 31.41 grams, carbohydrates 73.28 grams, fiber 6.98 grams, water content 8.24 grams, and ash content 4.04 grams. Conclusion: Substituting the toman fishmeal formulation affects instant porridge's color, aroma, and taste. However, substituting the Toman fishmeal formulation does not affect the texture.